Analisis Ujian Nasional Dengan Beberapa Kebijakan IPOLESOSBUD (BIDAYAH: STUDI ILMU-ILMU KEISLAMAN, 2017)
The paper aims to understand policies regarding national examination and those of IPOLESOSBUD, and examines them in explanatory-based discussion. The paper was written in May 2014 covering information obtained from focussed group discussion (FGD) followed by students of doctoral program in education who are school administrators from several provinces in Indonesia. Data and information collection was performed by class discussion, questionnaire, interview, and FGD. Then, the data was analyzed qualitatively. FGD results concluded that the national policy is problematic. National examination, basically, is against the essence, the function, and the goals of national education. In fact, national examination did not seem to have impact on advancing the quality of national education and creating the form of education that is able to actively encourage students to develop independently